Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1021/bm101486s
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State NMR Characterization of Autofluorescent Fibrils Formed by the Elastin-Derived Peptide GVGVAGVG

Abstract: The characterization of the molecular structure and physical properties of self-assembling peptides is an important aspect of optimizing their utility as scaffolds for biomaterials and other applications. Here we report the formation of autofluorescent fibrils by an octapeptide (GVGVAGVG) derived via a single amino acid substitution in one of the hydrophobic repeat elements of human elastin. This is the shortest and most well-defined peptide so far reported to exhibit intrinsic fluorescence in the absence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
66
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 48 publications
(126 reference statements)
11
66
1
Order By: Relevance
“…The similarities in the lifetime and spectral signatures between the three species are remarkable, given their differences in amino acid sequence and aggregate morphology. These findings substantiate the hypothesis made previously, that the intrinsic fluorescence phenomenon is a generic property of the cross β-sheet arrangement in amyloid fibrils,[5, 7] and is likely related to the extensive arrangement of hydrogen-bond networks running along the fibril axis [6]. Crucially, we also show that intrinsic fluorescence permits individual fibrils to be imaged microscopically without any use of extrinsic labels.…”
Section: Resultssupporting
confidence: 92%
“…The similarities in the lifetime and spectral signatures between the three species are remarkable, given their differences in amino acid sequence and aggregate morphology. These findings substantiate the hypothesis made previously, that the intrinsic fluorescence phenomenon is a generic property of the cross β-sheet arrangement in amyloid fibrils,[5, 7] and is likely related to the extensive arrangement of hydrogen-bond networks running along the fibril axis [6]. Crucially, we also show that intrinsic fluorescence permits individual fibrils to be imaged microscopically without any use of extrinsic labels.…”
Section: Resultssupporting
confidence: 92%
“…We examined the aggregation of soluble NSF under various destabilizing conditions and found that the transformation of native silk from a disordered random coil to highly ordered‐rich β‐sheet‐rich structure is accompanied by the conformation appearance of a fluorescence signal a in the blue–green region of the visible spectrum, which features a long fluorescence lifetime ( Figure 1 ). Interestingly, the observed spectral and lifetime characteristics are very similar to those reported for amyloid fibrils, such as amyloid‐β, lysozyme, and α‐synuclein, suggesting that there is a common structural origin for the intrinsic fluorescence in NSF and in amyloid fibrils, independent on the presence of a chemical chromophore. Moreover, we show that aggregation of native silk produces a material with remarkably strong and stable fluorescence characteristics.…”
Section: Introductionsupporting
confidence: 72%
“…But the fluorescent signal–to–noise ratio obtained for different crystals was variable and often not reproducible for the same crystals imaged at different times. Intrinsic blue–green fluorescence emission upon excitation with UVA light was previously observed for proteins in solution 33 , protein crystals and aggregates 43 , protein fibrils and matrix proteins 44, 45 , triethylamine and dendrimers containing amine/amide or imine groups ( 46 and references within). However, to the best of our knowledge, blue-green TPFE has not been used before to image protein crystals.…”
Section: Discussionmentioning
confidence: 79%